Managing the global supply chain : collection - Hill, Arthur V.; Autry, Chad Wheeler, 1970-; Goldsby, Thomas J.; Bell, John Edward, 1968- (Pearson Education, Inc. as FTPress Delivers, 2013)
The Encyclopedia of Operations Management (EOM) is an ideal 'field manual' for students, instructors, and practicing managers. For students, the EOM is a useful guide for developing an integrated mental map for the entire field of supply chain and operations management. It has also proven useful as a reference for students preparing for case discussions, exams, and job interviews. It is particularly helpful for students new to supply chain and operations management and for international students who need precise definitions of specialized terms. For instructors, the EOM is an invaluable desk reference and teaching aid that goes far beyond the typical dictionaries. Many instructors and doctoral students find the numerous figures, graphs, equations, Excel formulas, VBA code, and references helpful for their lectures and research. For practicing managers, the EOM is a valuable tool for black belt and green belt training programs and a powerful tool for helping organizations build a precise standard language.